In vitro activity of miltefosine in combination with voriconazole or amphotericin B against clinical isolates of Scedosporium spp. Issue 3 (March 2015) - Compain, Fabrice; Botterel, Françoise; Sitterlé, Emilie; Paugam, André; Bougnoux, Marie-Elisabeth; Dannaoui, Eric
Abstract : Abbreviations: FICI, fractional inhibitory concentration index.